CODE SWITCHING AND CODE MIXING ON CHINA RICH GIRLFRIEND NOVEL BY KEVIN KWAN - Lisa Agustiyana Budi; Surya Sili; Chris Asanti (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2021)
This research aimed to find the classification of code switching and code mixing types, and the identification of the reasons that indicated the characters performing code switching and code mixing in the novel entitled China Rich Girlfriend by Kevin Kwan. The researcher used qualitative and content analysis approach in analyzing and interpreting the data. The data source of this research was China Rich Girlfriend novel and data were generated from the dialogues and utterances by the characters which contained the practice of code switching and code mixing. Through the finding of the analysis, there were 87 practices of code switching which is divided into three types. Those are intra-sentential switching, inter-sentential switching and tag switching. And there were 60 practices of code mixing which is known as insertion, alternation and congruent lexicalization. The reasons of the characters performing code switching and code mixing are talking about particular topic, interjection, quoting somebody else, being emphatic about something and expressing group identity.